A proposed educational curriculum to develop the shooting skill of jumping with a basketball Experimental research on the students of the fourth stage / College of Physical Education for Girls For the academic year 2005-2006 (Journal of the College of Basic Education, 2023)
The sport has taken rapid progress in recent years, as a result of the developmentIn the foundations and theories of different sciences in general, and motor learning in particular, being the foundationto improve the mathematical level by providing learners with information about the efficiency oftheir performance in order to bring them to the required level of performance as a result of practice, training and repetition.The skill of shooting from a jump is one of the basic offensive skills of football players.Basket The researcher taught and trained the shooting skill by jumping with basketball for the year 2005-2006 through the preparation of a proposed curriculum for teaching this skill.In order to study this problem, the researcher assumed that there are statistically significant differences betweenCardiac tests and post-tests as a result of the impact of the proposed educational curriculum.